CONCEPT OF WELFARE AND ITS CRITERIA - Kasanov Rajabboy Toksanovich (Journals Park Publishing, 2025)
This article reveals the essence, criteria and social importance of a prosperous life. Through the article, the importance of this process to the social environment and justice of the society, which affects the development of the prosperous life, is considered. The article examines the factors affecting the development of the concept of a prosperous life, as well as the importance of this concept for the social stability and justice of society. Studies have shown that the concept of a prosperous life is not limited to economic development, but also includes human social, spiritual and ecological needs.
Keywords: Well-being, criterion, social stability, scientific research, economic stability, social welfare, social justice, method and methodology, cultural development, ecological stability, spiritual stability.